2013
DOI: 10.1063/1.4793597
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of the differences in diffusivity of the components of the metallic glass Pd43Cu27Ni10P20

Abstract: Bartsch et al. [A. Bartsch, K. Rätzke, A. Meyer, and F. Faupel, Phys. Rev. Lett. 104, 195901 (2010) The same model also explains the correlation between property of the β-relaxation with fragility found in the family of (Ce x La 1-x ) 68 Al 10 Cu 20 Co 2 with 0≤x≤1.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…25,[39][40][41][42][43] There are, however, very few data sets available over wide concentration or water activity ranges and our understanding of the breakdown of SE in these types of systems is thus relatively poor. Very similar results to those reported for aqueous mixtures have been found also for multi-component metallic glassy alloys [44][45][46][47] for which the diffusion behaviour of individual atomic species of different size were found to vary significantly. As an example, a recent study on a metallic glassforming alloy found that the larger atomic species followed the SE relation even in the deeply supercooled range, whereas the smaller atomic species decoupled dramatically and showed 4 orders of magnitude difference from the SE prediction based on their size.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…25,[39][40][41][42][43] There are, however, very few data sets available over wide concentration or water activity ranges and our understanding of the breakdown of SE in these types of systems is thus relatively poor. Very similar results to those reported for aqueous mixtures have been found also for multi-component metallic glassy alloys [44][45][46][47] for which the diffusion behaviour of individual atomic species of different size were found to vary significantly. As an example, a recent study on a metallic glassforming alloy found that the larger atomic species followed the SE relation even in the deeply supercooled range, whereas the smaller atomic species decoupled dramatically and showed 4 orders of magnitude difference from the SE prediction based on their size.…”
Section: Introductionsupporting
confidence: 87%
“… 22 , 29 This interpretation has recently been questioned based both on experimental and computer simulation observations. 46 , 47 , 57 Other suggested explanations instead propose that the SE breakdown arises due to differences in how translational diffusivity and viscosity (or structural relaxation) couple to spatially varying intermolecular cooperativity, and/or due to a link between translational diffusion and the secondary β-relaxation mechanisms that emerge as the glass transition is approached. 45 , 47 It is clear that we do not fully understand diffusion near and within the glassy state, and this is particularly emphasised for multi-component glass-forming systems.…”
Section: Introductionmentioning
confidence: 99%
“…If the Kohlrausch function is used to describe the correlation function of the α-relaxation, then τ α is much longer and n is larger for DEP in the mixture than in neat DEP. This increase of n or width of the α-dispersion of DEP in the mixture originates from stronger intermolecular coupling [23,26,46]. This is the primary cause of the larger width the α-loss peak of DEP in the mixture than in neat DEP, according to the CM description of component dynamics in binary mixtures and polymer blends.…”
Section: Johari-goldstein Relaxation Of Flexible Polar Probes In Apolmentioning
confidence: 95%
“…In addition to the primary (a-) relaxations that are responsible for the viscous flow, a kind of secondary relaxation, called Johari-Goldstein or b-relaxation [7][8][9] , often exists at high frequencies or low temperatures. Recent studies have demonstrated that b-relaxations are an intrinsic and universal feature of supercooled liquids and glasses 1,8,10 , and they are of significance to the understanding of many key issues in glassy physics and material sciences 1 , ranging from glass transition phenomenon [10][11][12][13] , diffusions [14][15][16][17] , physical aging 18,19 to mechanical properties 20,21 and mechanisms of plastic deformations [21][22][23] , as well as the stabilities and crystallization of glassy materials [24][25][26] .…”
mentioning
confidence: 99%